TANTANGAN DALAM PEMBELAJARAN PERGURUAN TINGGI DAN IMPLEMENTASI MERDEKA BELAJAR DI MASA PANDEMI COVID-19 - Endang Kartini; Lalu mimbar; Izrawati (LPPM Universitas Gunung Rinjani, 2021)
This study aims to determine the challenges of higher education learning and the implementation of independent learning during the Covid-19 pandemic. The method used in this research is literature study or library research. Literature studies are carried out by reading library sources to obtain the required data. The data sources used are secondary data, where secondary data is collected through textbooks, scientific journals, and perodical. The results showed that online learning is learning that uses an internet-based interactive model and a Learning Management System (LMS). The abilities of lecturers and students in online learning vary, some are accustomed to it, cannot be separated, there are also those who are forced and unprepared. However, the condition of the plague forces everyone to be ready to take advantage of information technology to prevent the outbreak from spreading. The Coronavirus Disease (Covid-19) pandemic has great potential to become a catalyst in the implementation of the Merdeka Learning: Merdeka Campus policy. Lecturers and students become actors in independent learning with the help of information technology. The implementation of online learning is not only dominated by State Universities (PTN), Private Universities (PTS) have also implemented online lectures well. For example, STIEAMM, which already has an online learning facility using an LMS platform with a display and URL: https://stieamm.ecampuz.com The implementation of online learning is not only dominated by State Universities (PTN), Private Universities (PTS) have also implemented lectures online well. For example, STIEAMM, which already has an online learning facility using the LMS platform with display and URL: https://stieamm.ecampuz.com Keywords: Challenges in Learning, Implementation of Free Learning During the Covid-19 Pandemic Abstrak Penelitian ini bertujuan untuk mengetahui tantangan pembelaran perguruan tinggi dan Implementasi Merdeka Belajar di Masa Pandemi Covid-19. Metode yang digunakan dalam penelitian ini adalah studi literature atau penelitian kepustakaan. Studi literature dilakukan dengan membaca sumber-sumber kepustakaan untuk memperoleh data yang diperlukan Sumber data yang digunakan berasal dari data sekunder, dimana data sekunder tersebut dikumpulkan melalui buku teks, jurnal ilmiah, perodical. Hasil penelitian menunjukkan bahwa Pembelajaran daring adalah pembelajaran yang menggunakan model interaktif berbasis internet dan Learning Manajemen System (LMS) Kemampuan dosen dan mahasiswa dalam pembelajaran daring beragam, ada yang telah terbiasa, tak lepas masih ada juga yang terpaksa dan tidak siap. Namun, kondisi wabah memaksa semuanya harus siap memanfaatkan teknologi informasi untuk mencegah wabah meluas. Pandemi Coronavirus Disease (Covid-19) justru memberikan potensi besar menjadi katalis dalam implementasi kebijakan Merdeka Belajar: Kampus Merdeka. Dosen dan mahasiswa menjadi actor dalam pembelajaran secara mandiri dengan bantuan teknologi informasi. Implementasi pembelajaran daring bukan hanya didominasi Perguruan Tinggi Negeri (PTN), Perguruan Tinggi Swasta (PTS) juga telah mengimplementasikan kuliah daring dengan baik. Misalnya, STIE AMM, yang telah memiliki sarana pembelajaran daring menggunakan platform LMS dengan tampilan dan URL: https://stieamm.ecampuz.com Kata Kunci : Tantangan Dalam Pembelajaran,Implementasi Merdeka Belajar Di Masa Pandemi Covid-19